Eletrodo de pasta de carbono modificado com solvente eutético profundo hidrofóbico e sua aplicação voltamétrica - Augusto, Karen Kenlderi de Lima (2021)
In this work, the use of hydrophobic deep eutectic solvent was proposed for the modification of carbon paste electrodes. Different HDES were prepared using fatty acids: octanoic, decanoic, and dodecanoic acids, and tetrabutylammonium bromide, and 1-octanol. The electrical conductivities and the water content of these HDES were determined, and the HDES and their precursors were characterized by FTIR(ATR). The HDES TBABr:DecA (1:2 mol/mol) showed better electroanalytical performance in modifying the proposed electrode, therefore was selected as a modifier/ binder in the preparation of carbon pastes. The modified electrode was morphologically characterized and, it was observed changes in its morphology resulting from the incorporation of HDES in the carbon paste. The electroanalytical performance of the electrodes was evaluated and characterized using cyclic and square wave voltammetry. Moreover, electrochemical impedance spectroscopy studies were carried out using hydroquinone as the electrochemical probe. Studies were carried out to optimize the amount of HDES in the pastes, pH, support electrolyte type, and instrumental parameters of the square wave voltammetry technique. In studies by electrochemical impedance spectroscopy, lower values of Rct (322 Ω), and higher values of k0 e kapp, 1.42×10-4 cm s-1e 1.65×10- 4 cm s-1, respectively, were obtained for the modified electrode. Using square wave voltammetry technique, the analytical curve for hydroquinone was linear in the concentration range of 1.50×10-5 to 2.04×10-3 mol L-1, with limits of detection and quantification of 4.59×10-6 mol L-1 and 1.53×10-5 mol L-1, respectively. In repeatability studies (inter and intra-days) and, potential interference, the proposed method showed to be precise and selective. The accuracy of the proposed method was evaluated by determining hydroquinone in dermatologic creams. The results were compared with those obtained using the comparative method by UV-Vis spectrophotometry.